Heterogeneous Single‐Atom Catalyst for Visible‐Light‐Driven High‐Turnover CO2 Reduction: The Role of Electron Transfer - Gao, Chao; Chen, Shuangming; Wang, Ying; Wang, Jiawen; Zheng, Xusheng; Zhu, Junfa; Song, Li; Zhang, Wenkai; Xiong, Yujie (Advanced materials (Weinheim), 2018)
Visible‐light‐driven conversion of CO2 into chemical fuels is an intriguing approach to address the energy and environmental challenges. In principle, light harvesting and catalytic reactions can be both optimized by combining the merits of homogeneous and heterogeneous photocatalysts; however, the efficiency of charge transfer between light absorbers and catalytic sites is often too low to limit the overall photocatalytic performance. In this communication, it is reported that the single‐atom Co sites coordinated on the partially oxidized graphene nanosheets can serve as a highly active and durable heterogeneous catalyst for CO2 conversion, wherein the graphene bridges homogeneous light absorbers with single‐atom catalytic sites for the efficient transfer of photoexcited electrons. As a result, the turnover number for CO production reaches a high value of 678 with an unprecedented turnover frequency of 3.77 min−1, superior to those obtained with the state‐of‐the‐art heterogeneous photocatalysts. This work provides fresh insights into the design of catalytic sites toward photocatalytic CO2 conversion from the angle of single‐atom catalysis and highlights the role of charge kinetics in bridging the gap between heterogeneous and homogeneous photocatalysts. Single‐atom Co sites coordinated on partially oxidized graphene nanosheets can serve as a highly active and durable heterogeneous catalyst for CO2 conversion, wherein the graphene bridges homogeneous light absorbers with single‐atom catalytic sites for the efficient transfer of photoexcited electrons. This design enables a turnover frequency of 3.77 min−1, superior to those obtained with conventional heterogeneous photocatalysts.